1997
DOI: 10.1016/s0149-7634(96)00049-8
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in the Human Corpus Callosum: Myth or Reality?

Abstract: Abstract:It has been claimed that the human corpus callosum shows sex differences, and in particular that the splenium (the posterior portion) is larger in women than in men. Data collected before 1910 from cadavers indicate that, on average, males have larger brains than females and that the average size of their corpus callosum is larger. A meta-analysis of 49 studies published since 1980 reveals no significant sex difference in the size or shape of the splenium of the corpus callosum, whether or not an appr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
160
1
14

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 331 publications
(191 citation statements)
references
References 98 publications
14
160
1
14
Order By: Relevance
“…Interestingly, these are the regions where axons interconnecting the prefrontal cortex cross the midline 98 ( Figure 1). The study mentioned 83 concurs with the report of a reduced CC size in women 76 in drawing attention to sex-related differences in the neuropathology of S. Nevertheless, given the long history of controversial results with respect to sex differences in CC size, 96 the data mentioned must be considered with prudence. It should be added that counting callosal axons in A = acute, B = boys, C = chronic, ES = early onset S (o35 y), F = females, F>M = more numerous females, G = girls, lh = left handed, LS = late onset (>50 y), SM = males, pS = at risk for schizophrenia, rh = right handed, S = schizophrenics, SPD = schizotypal personality disorder.…”
Section: Morphological Studiessupporting
confidence: 77%
See 1 more Smart Citation
“…Interestingly, these are the regions where axons interconnecting the prefrontal cortex cross the midline 98 ( Figure 1). The study mentioned 83 concurs with the report of a reduced CC size in women 76 in drawing attention to sex-related differences in the neuropathology of S. Nevertheless, given the long history of controversial results with respect to sex differences in CC size, 96 the data mentioned must be considered with prudence. It should be added that counting callosal axons in A = acute, B = boys, C = chronic, ES = early onset S (o35 y), F = females, F>M = more numerous females, G = girls, lh = left handed, LS = late onset (>50 y), SM = males, pS = at risk for schizophrenia, rh = right handed, S = schizophrenics, SPD = schizotypal personality disorder.…”
Section: Morphological Studiessupporting
confidence: 77%
“…Furthermore, CC size should probably be corrected for total brain size, but although several methods exist, none is fully satisfactory. 96 Also, if the decreased CC is due to loss of callosal axons (below) and this significantly contributes to decreasing brain size (for example, by reducing the volume of the neuropil, that of the white matter, or of the cortical neurons), the correction would, in fact, tend to obscure the finding. Finally, the studies exploring regional differences in CC size are particularly difficult to interpret since methods of CC partitioning vary across studies (reviewed in Bishop and Wahlstein 96 ), including in S research, and the size of the CC partitions can be influenced by CC shape.…”
Section: Morphological Studiesmentioning
confidence: 99%
“…There is not much reason to assume that the CC functions in a predominantly inhibitory fashion in males and a predominantly excitatory fashion in females. While some researchers have claimed that the female CC, if scaled relative to whole brain size, is larger and thus facilitates transfer of information between the hemispheres (Oka et al, 1999; Mitchell et al, 2003), others have not found a difference (Bishop and Wahlsten, 1997; Luders et al, 2006; Zarei et al, 2006). Thus, there is little reason to speculate on the possibility of males and females differing with regard to the relation of tinnitus to callosal structure and function.…”
Section: Discussionmentioning
confidence: 99%
“…When a new claim is made of weak allele association or linkage with some other measure (such as IQ), experience should caution us against premature enthusiasm until the result is replicated adequately and survives meta-analysis. Otherwise, there arises a serious risk that false claims will mislead public discourse, as allegations of sex-based differences in the human brain (Bishop & Wahlsten 1997) and an alleged relation between serotonin metabolism and impulsive violence (Balaban et al 1996) have already done.…”
Section: Allele Association Studiesmentioning
confidence: 99%